Grid-Based Characterization and Sustainable Planning for Fractured Urban Textures: A Case Study of Nanhao Village in Baotou - Haoyu Tian; Weidong Wang; Ting Hao (Buildings)
During urban development, significant contrasts between urban villages and their surrounding areas lead to the emergence of fragmented urban spaces, dysfunctionalities, cultural barriers, and, ultimately, to the formation of fractured urban textures centered on urban villages (FUT-UVs). The fractured urban textures of an FUT-UV create a disconnect from the surrounding urban area, isolating it from the city. This separation significantly impacts the daily lives and interactions of its residents. To address this and support more sustainable urban development, a thorough and multi-dimensional understanding of FUT-UVs is of crucial importance. This study examines Nanhao Village in Baotou City, conducting a quantitative analysis of key indicators related to buildings, roads, and functional facilities. Using overlay analysis, it explores the characteristics of the FUT-UV, the interactions between these indicators, and opportunities for improvement. From these findings, strategies for reconnecting an FUT-UV with its surroundings are proposed. The results indicate that: (1) FUT-UVs are mainly characterized by low-rise, high-density developments with limited open space. Their road networks are narrow and congested, while accessibility remains low. Low-end businesses are concentrated in a single area within the village, showing minimal functional diversity; (2) FUT-UVs can increase construction intensity by raising the number of floors in buildings, and have higher building densities in the most accessible areas. This increase in density can effectively enhance functional diversity; and (3) improving road accessibility in FUT-UVs will allow for a smoother influx of external activity, enhancing functional diversity. Additionally, increasing the number of building floors intensifies construction, raises the density of functional facilities, and boosts urban vitality. Based on these characteristics of fragmentation and interactive mechanisms, this study suggests stitching strategies related to transportation, architecture, and functionality. This study introduces a new framework for analyzing urban texture, offering a detailed multi-faceted analysis of FUT-UV fragmentation and clarifying the interaction between FUT-UVs and surrounding urban forms. This study reinforces the coherence of the spatial form and the development of the functional economy of urban villages within the modern urban environment. It supports the sustainable development of urban areas and promotes balanced growth between urban villages and their surrounding regions.